The origin of lipid droplets in the post-pharyngeal gland of Dinoponera australis (Formicidae: Ponerinae) - Caetano, Flávio Henrique [UNESP]; Zara, Fernando José [UNESP]; Gregório, Elisa Aparecida [UNESP] (International Society of Cytology, 2002)
The post-pharyngeal gland of normal and starvation ants was studied under TEM. This study showed an orgin of lipids droplets from mitochondria (named derivate mitochondria) in the normal ants and the lipids absence or reduction, in fasting ants.
Keywords: Ants; Dinoponera; Lipid droplets; Mitochondria; PPG; Dinoponera australis; Formicidae; Ponerinae